Circulating Levels of Interleukin-1 Family Cytokines in Overweight Adolescents - Christian Jung; Norbert Gerdes; Michael Fritzenwanger; Hans Reiner Figulla (Hindawi Limited, 2010)
Objectives. Obesity and related diseases are dramatically increasing problems, particularly in children and adolescents. We determined circulating levels of different interleukin (IL)-1 family members in normal weight and overweight adolescents. Methods. Seventy male, Caucasian adolescents (13-17 years) were recruited. Thirty-five had a body-mass index (BMI) above the 90th age-specific percentile. IL-1α, IL-1β, IL-1 receptor antagonist (IL-1ra), and IL-18 were determined using multiplex-technology. Results. IL-18 concentrations were higher in the overweight group compared to normal weight (161.6±40.7 pg/ml versus 134.7±43.4 pg/ml, P=.009). Concentrations of circulating IL-1β levels were below the detection threshold. IL-18 (R2:0.355, P<.01) and IL-1ra (R2:0.287, P<.05) correlated with BMI, whereas IL-1α did not. Conclusions. Accumulating data indicate the importance of the endocrine function of adipose tissue for the pathophysiological consequences of obesity-related co-morbidities. Since IL-18 is involved in the pathogenesis of different cardiovascular diseases, we conclude that IL-18 may represent a link between obesity and related co-morbidities in children and adolescents.